Novel mouse model of cardiopulmonary bypass. (18th July 2017) - Madrahimov, Nodir; Boyle, Erin C; Gueler, Faikah; Goecke, Tobias; Knöfel, Ann-Kathrin; Irkha, Valentyna; Maegel, Lavinia; Höffler, Klaus; Natanov, Ruslan; Ismail, Issam; Maus, Ulrich; Kühn, Christian; et al.
Abstract: OBJECTIVES: Cardiopulmonary bypass (CPB) is an essential component of many cardiac interventions, and therefore, there is an increasing critical demand to minimize organ damage resulting from prolonged extracorporeal circulation. Our goal was to develop the first clinically relevant mouse model of CPB and to examine the course of extracorporeal circulation by closely monitoring haemodynamic and oxygenation parameters. METHODS: Here, we report the optimization of device design, perfusion circuit and microsurgical techniques as well as validation of physiological functions during CPB in mice after circulatory arrest and reperfusion. Validation of the model required multiple blood gas analyses, and therefore, this initial report describes an acute model that is incompatible with survival due to the need of repetitive blood draws. RESULTS: Biochemical and histopathological assessment of organ damage revealed only mild changes in the heart and lungs and signs of the beginning of acute organ failure in the liver and kidneys. CONCLUSIONS: This new CPB mouse model will facilitate preclinical testing of therapeutic strategies in cardiovascular diseases and investigation of CPB in relation to different insults and pre-existing comorbidities. In combination with genetically modified mice, this model will be an important tool to dissect the molecular mechanisms involved in organ damage related to extracorporeal circulation.